Effective Holistic Approaches to Reducing Nurse Stress and Burnout During COVID-19. Issue 5 (May 2022) - Pagador, Florida; Barone, Melanie; Manoukian, Mana; Xu, Wenrui; Kim, Linda
ABSTRACT: Background: Prolonged exposure to work-related stress can lead to nurse burnout, potentiating clinical and medication errors and low-quality patient care. Holistic approaches (such as mindfulness training, "zen rooms, " and massage chairs, among others) have been shown to reduce nurses' anxiety, stress, and burnout. Purpose: To evaluate the use of "serenity lounges" (dedicated rooms where nurses can take workday breaks for the purposes of relaxation and rejuvenation) and massage chairs on nurses' anxiety, stress, and burnout. Methods: This quality improvement project analyzed 67 paired responses to surveys filled out by nurses before and after their use of serenity lounges at a medical center in Los Angeles between November 2020 and May 2021. Following successful implementation of a serenity lounge on a pilot unit, this project was expanded to a total of 10 units, including COVID-19 cohort units. As part of this expansion, massage chairs were added to 10 serenity lounges, along with items such as wipes, gloves, and shoe covers to enable nurses to adhere to infection control protocols. Results: Analysis of the 67 paired responses to pre- and post-lounge-use surveys revealed a significant reduction in feelings of emotional exhaustion, burnout, frustration, being worn out, stress, and anxiety after use of the serenity lounge. Improvements in feelings of emotional exhaustion, being worn out, and being anxious were also noted after using the massage chair for at least 10 to 20 minutes. Conclusions: These results highlight the importance of providing a holistic approach, including a serene space, massage equipment, and other amenities, to help nurses reduce feelings of anxiety, stress, and burnout, particularly during challenging times such as the COVID-19 pandemic. Abstract : This quality improvement project evaluated the use of serenity lounges—dedicated rooms where nurses can take workday breaks to relax and rejuvenate—and massage chairs on nurses' anxiety, stress, and burnout.